Planetary Rent Gaps. (22nd September 2015) - Slater, Tom
Abstract: In this paper I recapitulate the origins, structure, and purpose of Neil Smith's rent gap theory, and assess the frequently discussed but rarely dissected empirical studies of rent gaps, in order to trace the key analytical and political shifts Smith effected (from consumer preference to mortgage capital circulation, from "natural areas" to state structures, from house prices to capital depreciation, and from middle class demand to class struggle), as well as posit some possible extensions of the theory vis à vis territorial stigmatisation and displacement. This tracing and extending in place, I then consider the rent gap in the context of the emerging body of work on planetary urbanisation, and argue that the theory helps to expose and confront new geographies of structural violence—planetary rent gaps—where the constitutive power of speculative landed developer interests in processes of capitalist urbanisation can be analysed and challenged. If, as David Harvey has recently argued, rent "has to be brought forward into the forefront of analysis … [to] bring together an understanding of the ongoing production of space and geography and the circulation and accumulation of capital" (2010:183, The Enigma of Capital and the Crises of Capitalism, Profile), then it is important to consider what we can learn from the rent gap today, rather than relegate it, as so many seem to do, to something that has already been debated or exhausted in the large literature on gentrification.